Habib Ahmed's maqāṣid sharī`ah concept on cooperative regulations in Indonesia - Zulfikar Zulfikar (State Institute of Islamic Studies (IAIN) Salatiga, 2021)
This article discussed Habib Ahmed's maqāṣid sharī`ah concept on Islamic Financial Institutions (IFIs) contracts, regarding the dualism of cooperative regulations in Indonesia between sharia and non-sharia-based cooperatives. In initiating the NIE (New Institutional Economics) approach for IFIs, Habib Ahmed emphasized the vital role of embeddedness as a culture rooted in the knowledge system. This embeddedness is the starting point of IFIs adaptation. These informal institutions then influence the formation of formal institutions and are followed by institutional forms of organization. Finally, the transaction products are in line with the organizational form. In other words, according to Habib Ahmed, if the adaptation and transaction of the IFIs start from this stage, then the product will be entirely in line with the proper Islamic ontology and epistemology. This qualitative library research focused on the reality of cooperatives in Indonesia, assessed from Habib Ahmed's perspective. This study concluded that Indonesia's economy still does not represent the goal of its constitutional economy with a feeling of kinship and mutualistic organization, such as cooperatives. In addition, its significant economic growth, which places it in the top twenty countries (G-20) in Gross Domestic Product (GDP), is not inclusive.